Senyawa Aktif Sayuran Cruciferae dan Perubahan Kadar Kolesterol serta Vitamin C pada Tikus Hiperkholesterolemia - Endang Sri Sunarsih; Lukman Hakim; Sugiyanto Sugiyanto; Sumantri Sumantri (MEDIA MEDIKA INDONESIANA, 2011)
ABSTRACTActive compounds of cruciferae family and the change of total cholesterol level and vitamine C in hipercholesterolaemic ratsBackground: Cauli flower is a member of the Cruciferae family. One of the active compound content of indole-3-carbinol, is used to prevent and treat cancer. Vitamine C in the cauli flower as an antioxidant is able to avert free radicals that are formed in aerobic organisms and hipercholesterolaemic condition. The study aimed to determine the active compounds contained in the of cauli flower and its role in changing of the lipid profile and vitamine C levels in hipercholesterolaemic rats.Methods: To identify up the active compounds of cauli flower by maceration repeately, with alcohol: ammoniak (19:1). The results were determinated by thin layer chromatography (TLC). Spotting results obtained were compared with standard spots in its color reaction and Rf spots with Rf standard samples. Twenty rats were divided into 4 groups, and made hipercholesterolaemic, group I as a negative control, group II as a positive control were given green tea 0.605 g/kgBW, group III-IV were given cauli flower juice for 14 days dose of 10 and 15 ml/kgBW, the blood were analyzed for total cholesterol level and vitamine C plasma.Results: Cauli flower active compounds are indole-3-carbinol, indole-1-3-carbinol, indole-3-carboxylic acid and sulforafan they were capable of decreasing total cholesterol levels to 45%, and increasing plasma vitamine C level by 55% compared to before treatment.Conclusion: Cauli flower contains 4 indoles, and is able to decrease total cholesterol and increase vitamine C plasma in hipercholesterolaemic rats.Keywords: Cruciferae, indole, TLC, cholesterol, vitamine CABSTRAKLatar belakang: Bunga kubis, termasuk keluarga Cruciferae. Salah satu kandungan senyawa aktifnya indol-3-karbinol, mampu mencegah dan mengobati penyakit kanker. Vitamin C yang terdapat di dalam bunga kubis sebagai antioksidan mampu menangkal radikal bebas yang terbentuk pada organisme aerobik, kondisi hiperkolesterolemia. Penelitian ini bertujuan untuk mengetahui senyawa aktif yang terkandung dalam bunga kubis (Brassica Oleracea var Botrytis L) dan perannya dalam mengubah profil lipid dankadar vitamin C pada tikus hiperkolesterolemia.Metode: Untuk menyari senyawa aktif bunga kubis dilakukan macerasi berulang, dengan alkohol: ammoniak (19:1). Hasil penyarian dilakukan penetapan senyawa aktif secara kromatografi lapis tipis (KLT). Hasil bercak yang diperoleh dibandingkan dengan bercak standar dengan membandingkan reaksi warna dan Rf bercak sampel dengan Rf standar.Untuk mengamati efek farmakologi, 20 ekor tikus dibagi menjadi 4 kelompok, dibuat hiperkolesterolemia, kelompok I sebagai kontrol negatif, kelompok II sebagai kontrol positif diberi teh hijau 0,605 g/kgBB, kelompok III-IV diberi jus bunga kubis bunga selama 14 hari dosis 10 ml/kgBB dan 15 ml/kgBB, data darah dianalisis kadar kholesterol total serum dan vitamin C plasma.Hasil: Bunga kubis (Brassica Oleracea var Botrytis L) mengandung senyawa aktif: indol-3-karbinol, indol-1-3-karbinol, indol-3- asam karboksilat dan sulforafan yang mampu menurunkan kadar kolesterol total serum sampai 45% dan meningkatkan kadar vitamin C plasma sampai 55% dibanding sebelum perlakuan.Simpulan: Bunga kubis mengandung 4 senyawa indol dan mampu menurunkan kolesterol total serum dan meningkatkan vitamin C plasma pada tikus hiperkolesterolemia